PENINGKATAN DAYA SAING UMKM INDONESIA: TANTANGAN DAN PELUANG PENGEMBANGAN IPTEK - iwan ridwan zaelani (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2019)
Small and Medium Enterprises (SMEs), have an important role in the economic development of a country, including Indonesia. In addition to its fairly good development, this sector also has a significant contribution to the opportunities for more extensive employment opportunities, increased foreign exchange, income tax and sales as well as opportunities for human resource development. But on the other hand, although the number of SMEs in Indonesia is very large, and its ability to support the national economy is undoubtedly, its existence is still not